2013
DOI: 10.1136/oemed-2013-101873
|View full text |Cite|
|
Sign up to set email alerts
|

Bladder cancer incidence among workers exposed too-toluidine, aniline and nitrobenzene at a rubber chemical manufacturing plant

Abstract: Background An earlier investigation found increased bladder cancer incidence among workers at a rubber chemical manufacturing plant that used o-toluidine, aniline and nitrobenzene. The cohort was expanded to include additional workers (n=1875) and updated through 2007 to assess bladder cancer with improved exposure characterisation. Methods Work histories were updated and exposure categories and ranks were developed for o-toluidine, aniline and nitrobenzene combined. Incident cancers were identified by linka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 21 publications
2
47
1
2
Order By: Relevance
“…27 A recent cohort study considered o-toluidine to be responsible for the increased bladder cancer incidence among workers at a chemical manufacturing plant. 28 Hb adducts of toluidines in smokers versus non-smokers have been measured previously. 29 30 The results showed that smokers have significantly higher o- and p-toluidine concentrations than non-smokers, but no significant differences were seen for m-toluidine.…”
Section: Discussionmentioning
confidence: 99%
“…27 A recent cohort study considered o-toluidine to be responsible for the increased bladder cancer incidence among workers at a chemical manufacturing plant. 28 Hb adducts of toluidines in smokers versus non-smokers have been measured previously. 29 30 The results showed that smokers have significantly higher o- and p-toluidine concentrations than non-smokers, but no significant differences were seen for m-toluidine.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Therefore, our study confirmed the increased risk of urothelial cancer for those working in the rubber manufacturing 2 15 which combines several urinary tract carcinogens such as o -toluidine, aniline and nitrobenzene. 8 However, we also demonstrated the highest increased risk for roadwork and building industry which is not recognised by the current recommendations. 2 Thus, we also promote to screen roadwork and building industry workers with urine cytology.…”
Section: Discussionmentioning
confidence: 59%
“…Among potential urothelial carcinogens existing, three classes were recognised: aromatic amines 6 (such as benzidine, 7 aniline, o -tolidine, o -toluidine, 8 9 10 beta naphtylamine 7 ), polycyclic aromatic hydrocarbons (such as benzene, 12 13 38 benz(a)pyrene 11 ) and nitrosamines (such as nitrobenzene 8 ). They were used in various occupational sectors such as rubber manufacturing, 7 10 13–15 chemical and pharmaceutical industry, 7 dye manufacturing, 6 7 15 textile, 15 plastic, leather and tanning industry, roadwork industry, 13 metalworkers, 16 metalworking fluids, 17 18 aluminium, 19 foundries.…”
Section: Discussionmentioning
confidence: 99%
“…Aniline (CID000006115) consists of a phenyl group attached to an amino group, and it is the precursor of industrial chemicals. It is reported that the incidence of bladder cancer is clearly related to exposure to aniline [ 59 ]. Potential reasons might be due to an increase in iron overload in the spleen and upregulation of TNF- α , IL-1, and IL-6.…”
Section: Resultsmentioning
confidence: 99%